Toward a Beech-Dominated Alternative Stable State in Dinaric Mixed Montane Forests: A Long-Term Study of the Pecka Old-Growth Forest - Diaci, Jurij; Adamic, Tomaz; Fidej, Gal; Rozenbergar, Dusan (Frontiers in Forests and Global Change, 2022)
In the last century, a synchronous beech expansion has been observed for many mixed mountain forests in southeastern Europe. This change is associated with the interaction of various disturbances. We analyzed structural changes in the Pecka old-growth forest in Slovenia during the last century, using several inventories of the tree layer, regeneration, and site factors. Throughout the observation period, the density of silver fir in the regeneration layer and in the overstory steadily decreased. In 1893, silver fir accounted for about 60% of the growing stock, whereas in 2013 it accounted for less than 13%. This is likely because of silver fir's decline in the canopy layer due to air pollution, successive windthrows and overbrowsing. However, climate change may also have played an important role, as silver fir also declined in southeastern European old-growth forests where air pollution was less pronounced and ungulate densities were low. A gradual decline of silver fir in the overstory resulted in a decrease of overall tree density to 231 trees ha-1, while growing stock remained relatively high at 712 m3 ha-1. Median diffuse light at 1.3 m was 3.7% and regeneration density was 19,954 ha-1. Beech was dominant (94%), followed by silver fir (4%) and sycamore maple (2%). No silver fir seedlings larger than 0.2 m were recorded. Silver fir, sycamore maple, and beech regeneration showed 87%, 76% and 45% browsing damage, respectively. Regression models indicated some evidence of niche partitioning between silver fir and beech. However, many processes may be masked by the silver fir's avoidance strategy. Given current red deer densities, climate change, and existing forest structure, the Pecka old-growth forest will likely reach an alternative stable state dominated by beech in a few decades. This calls for immediate reduction of ungulate populations. Despite the interaction of multiple disturbances, the Pecka old-growth forest has maintained a relatively high overall growing stock, a favorable microclimate, and succession pathway with shade-tolerant beech. This indicates the intrinsic resilience of natural forests. The mechanisms discussed here can be applied to the future governance of old-growth and managed montane mixed forests.